Access Control Android Application to Remotely Control PC - Agarwal, Shalabh; Sengupta, Sayantika; Sanyal, Swarnali; De, Naireeta (International Journal of Computer Sciences and Engineering, 2025)
Access Control is an Android Application that works on the concepts of wireless socket programming. Our main aim for developing this application is to provide the user with a remote for his/her PC in the form of an android device. Using this application, the user may perform various actions on his PC such as controlling the mouse movement and operations, sliding through various PPT slides, managing media, entering text on any application on their PC, from a reasonable distance, all just with the help of their android device. In order for this application to work, the PC and the given android device need only be connected to a common network.